2021
DOI: 10.1101/2021.04.16.21255636
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating the effect of mobility on SARS-CoV-2 transmission during the first and second wave of the COVID-19 epidemic in Switzerland: a population-based study

Abstract: The effect of mobility and its value for surveillance in different waves of the COVID–19 epidemic is still unclear. In this study, we compared the role of mobility during the first and second epidemic wave in Switzerland by analysing the link between daily travel distances and the effective reproduction number Rt of SARS–CoV–2. Here we used aggregated mobile phone data from a representative panel survey of the Swiss population to measure human mobility. We estimated the effects of reductions in daily travel di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…We report our review according to the PRISMA 2020 statement 18 . A completed PRISMA 2020 checklist is provided in SI Appendix G. We conceptualized the review by drawing on experience from our own primary research in the field 4,97 . The search strategy was developed jointly and executed by an experienced information consultant.…”
Section: /46mentioning
confidence: 99%
“…We report our review according to the PRISMA 2020 statement 18 . A completed PRISMA 2020 checklist is provided in SI Appendix G. We conceptualized the review by drawing on experience from our own primary research in the field 4,97 . The search strategy was developed jointly and executed by an experienced information consultant.…”
Section: /46mentioning
confidence: 99%
“…The authors achieved that reopening schools during lockdown could lead to a substantial increase in virus transmission. Lison et al [24] investigated the relation between mobility, based on mobile phone information, and the propagation of the Sars-CoV-2 in Switzerland during the first and second waves. Using a regression model, the authors found that mobility reduction translates into a reduction of the disease spread.…”
Section: Introductionmentioning
confidence: 99%